A Study on the Space Characteristics of Ancient Ancestral Temples in the Taiping District of East China. Issue 3 (1st September 2016) - Chen, Kezhen; Li, Yunzhang; Cao, Yi
Abstract : The ancestral temple plays an important role in maintaining the lineage society in Huizhou, a historical region in East China′s Anhui Province. The study, based on surveys and drawings of seven ancient ancestral temples in the Taiping district, analyzes the overall layout characteristics, the interior space arrangement, exterior morphological characteristics and the social meaning of the space. Focusing on the peculiarity of the forms of those ancient ancestral temples, this research can provide valuable information in regard to the diversity of architectural forms within the same cultural circle.